Media Cultures and the Representation of Science in Korea and the United States: The BSE Case in 2008. Issue 3 (1st September 2017) - Bak, Hee-Je; Kleinman, Daniel Lee
Abstract : In 2008 the Korean government decided to resume importing US beef, leading to a nationwide controversy over the risk of bovine spongiform encephalopathy (BSE), or mad cow disease. Korean media coverage of BSE during this controversy demonstrates how media reporting on scientific matters interacts with political controversy over science-related risks. In Korea, where media organizations tend to be associated with particular political ideologies, the media emphasized the uncertainty of scientific accounts in the BSE case and reinforced the politicization of science by selectively mobilizing contrasting scientific claims and scientific authorities based on each media outlet's political position. The distinctive role of such a media culture in the science-related political discourse is further highlighted when we consider US media coverage of BSE risk during the same period: in that coverage, the baseline technical risk-related issues were taken for granted and the BSE controversy in Korea was presented largely as a trade issue.